Analysis of the need of flexibility in working lives of orthopaedy, physiotheraphy and rehabilitation doctors who work in universities’ research hospitals and private hospitals - Korkmaz, Murat; Kilic, Bulent; Talas, M.; Yucel, Ali Serdar (Asian Network for Scientific Information, 2015)
In today’s globalization conditions, the competitiveness of health sector is more prominent. Therefore, the physicians who actively participate in health sector have gained significant importance in terms of competition. This study examined the adaptation of orthopedists, physical therapists and rehabilitation specialists who are employed within the health sector to the working life. A total of 748 physicians from “Orthopedics, Physiotherapy and Rehabilitation” participated in the study. Cities of Istanbul, Ankara, Tekirdag, Bursa and Izmir constitute the target population of the study. A total of 58 public and private medical institutions were included. This number is the sample of the study. The study is an applied one and a questionnaire was used in the research. Reliability analysis was obtained following the general research and a coefficient of 0.963 was found after Cronbach Alpha. In addition to data obtained from the research, frequency tables, descriptive statistics, independent t test, Pearson correlation analysis, one-way variance analysis and Tukey test were utilized in the practice. It has been concluded following the research that the flextime provided to orthopedists, physical therapists and rehabilitation specialists working in training research, university and private hospitals increases the quality of life and accordingly effectiveness and performance level improves. © 2015 Asian Network for Scientific Information.
Keywords: Competition; Course of business; Flexible working; Health sector; Hospital; Law; Physician; Wage